2021
DOI: 10.3390/molecules26237361
|View full text |Cite
|
Sign up to set email alerts
|

The Mineral Composition of Date Palm Fruits (Phoenix dactylifera L.) under Low to High Salinity Irrigation

Abstract: Adaptability to salinity varies between different varieties of date palm trees. This research aims to explore the long-term impact of different salinity irrigation levels on the mineral content of 13 date palm varieties grown in the United Arab Emirates (UAE). Date varieties were grown using three irrigation water salinity levels of 5, 10 and 15 dS m−1. The mineral composition (B, Ca, Cu, Fe, K, Mg, Na, P and Zn) of date palm fruits was determined using Inductively Coupled Plasma-Optical Emission Spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…The results were similar to Table S2 results. The plant flesh was palm anbara date flesh consisted of minerals in the form of metal ions, , resulting in increased conductivity, which caused inhomogeneity in the magnetic field and affected the optimized pulse length of the 1 H hard 90° pulse because it is more sensitive to the ionic effect. Electrical noise produced by conductive substances can significantly lower the sensitivity of NMR probes.…”
Section: Resultsmentioning
confidence: 99%
“…The results were similar to Table S2 results. The plant flesh was palm anbara date flesh consisted of minerals in the form of metal ions, , resulting in increased conductivity, which caused inhomogeneity in the magnetic field and affected the optimized pulse length of the 1 H hard 90° pulse because it is more sensitive to the ionic effect. Electrical noise produced by conductive substances can significantly lower the sensitivity of NMR probes.…”
Section: Resultsmentioning
confidence: 99%
“…It also noted that the reality of date cultivation in Iraq and the challenges of this environment suffer from high water salinity, which is reflected negatively in the cultivation of this tree. Dghaim et al (2021) studied a group of Emirati dates and reported that the cause of changes in the mineral content of different date varieties was due to the conditions of salt stress, which is considered major environmental stress that affects plant growth and development. In addition, this study also showed that the effect of irrigation with saline water was directly reflected in the quality of the fruit, especially the mineral content of the fruits.…”
Section: Mineral Elements In the Fruits And Powder Of Dayeri And Zahdimentioning
confidence: 99%
“…Furthermore, coffee with palm date seeds is a good source of important nutrients [ 24 ]. It has significant concentrations of iron, calcium, magnesium, potassium, and other elements that are necessary to sustain physiological processes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%